(untitled) (Atti del Sodalizio Glottologico Milanese, 2021)
The paper focusses on Vittore Pisani’s considerations about the nature of language and speech. A renowned scholar in historical linguistics, Pisani made no specific contribution to theoretical topics. Nevertheless, in a series of passages from some of his papers the creative role of speakers and hearers is emphasized, and the observation is made that the products of their linguistic activity can be the models for new speech acts. For Pisani speech acts within a given social aggregate can be investigated to describe what they have in common at the various levels of analysis, and the results of this investigation can be organized into a “system of isoglosses”, which represent what is called a language. So, language is not an ideal entity with an autonomous existence and is organized regardless of the individual speech acts, but it is the result of a reconstruction that can vary according to the data on which it is based. Such a conception is in line with contemporary sociolinguistic and pragmatic research.